Perancangan Media Pembelajaran Berbasis Video Tutorial Mendesain Jaringan Lokal/LAN Kelas X TKJ - Mapicayanti, Deviana; Jamaludin, Jamaludin; Fathoni, Ahmad (Universitas Hamzanwadi, 2018)
The purpose of this study was to find out: (1) The Results of Designing Learning Media Based on Video Tutorials on Material Designing Local / LAN Networks For Class X Students of TKJ at 1 Sakra Vocational High School, (2) the level of feasibility of the developed learning media. This study is Research and Development research with ADDIE development model, namely (1) Analysys, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The assessment instrument for video tutorial-based learning media was in the form of a 5-scale questionnaire. The sources of the research data were 2 media experts, 2 material experts, and 33 students majoring in TKJ. The results of this study are the Design of Learning Media Based on Tutorial Videos on Material Designing Local / LAN Networks in Class X TKJ students at 1 Sakra Vocational High School, with a display in the form of intro, menu page, profile page, KI / KD page, 2 pages submenu material namely theory and videos, subject matter pages, learning goal pages, and quiz pages. Media Expert feasibility test results viewed from 2 aspects are categorized as Very Eligible (87%). And the test results from Material Experts fall into the category of Very Eligible (95%). Based on the response of media usage by 33 students of class X majoring in TKJ, it was categorized as Very Eligible (83%)